Hydroxy Gas (HHO) Supplement of Ethanol Fuel Mixture In A Single-Cylinder Spark-Ignition Matic-Engine - Gatot Setyono (Journal of Mechanical Engineering and Mechatronics, 2020)
Hydroxy Gas (HHO) has been identified as an efficient alternative energy source. HHO is considered an alternative fuel. It can be applied alone or mixed with other kind of fuels in different ratios. In this analysis, the composition of HHO-ethanol was mixed in different variations. Ethanol-HHO was chosen because of its high-octane rating yet low exhaust emissions, and ease of obtaining from engine products. It has been applied on fuel prepared by mixing it with gasoline in various ratios (E30-HHO, E40-HHO, and E50-HHO). The ethanol-HHO mixture has been used in a single-cylinder 4-stroke spark machine for performance, by varying speed of engine from 4000 to 9000 RPM and by applying a platinum spark plug electrode type. In experiments, engine power, average effective pressure (MEP), specific fuel consumption (SFC), and thermal efficiency have been analyzed. The analysis of combustion is accomplished by taking a pressure cycle in the chamber, monitoring the automatic control of engine control unit (ECU) and ensuring utilization in the same parameters of the various fuels tested, in addition to the fuel injection time, which increases with increasing ethanol percentage. Optimal power, MEP and thermal efficiency values are obtained with ethanol-gasoline (E50-HHO) mixture which is operated at 7200 rpm, an increase of about 5% compared to gasoline. Significant reduction in SFC was observed using HHO-ethanol mixture, reduced by about 6% compared to gasoline.